PROTOTYPE APPROACH TO HATE AND ANGER IN THE HEBREW BIBLE conceiving emotions - Grant, Deena E., 1977- (London : ROUTLEDGE, 2023)
This innovative book applies findings from the field of cognitive linguistics to the study of emotions in the Hebrew Bible. The book draws on the prototype approach to conceptual categories to help interpret emotion language in biblical passages. Contemporary scholarship has come to recognize that biblical emotion terms do not necessarily possess exact equivalents within our modern lexicons, even if some of these terms express (or appear to express) concepts similar to those conveyed by modern emotion language. In particular, the book focuses on sn' and rh, which are almost always equated in modern English with hate and anger. However, the ancient Hebrew roots evoke varied and robust emotion-scripts that are quite different than their English counterparts. We see how the prototype script model may help to expose the unique nuances of sn' and rh and put into profile elements of these emotions that may otherwise go unnoticed. Overall, the study demonstrates that even though modern emotion terms cannot fully capture the ancient emotional experience, our shared use of language to evoke meaning offers us entre into the emotional world represented in the Hebrew Bible.
Keywords: Bible. -- Criticism, interpretation, etc; Hate in the Bible; Anger in the Bible; RELIGION / General; RELIGION / Bible / General